Sosialisasi Buku Panduan Ergonomi “Learning From Home” dari Perhimpunan Ergonomi Indonesia Bagi Peserta Didik Sekolah Dasar di Kecamatan Cikeusal Kabupaten Serang - Deny Sunaryo; Yoga Adiyanto (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2020)
The Ergonomics Guide Book "Learning From Home" from the Indonesian Ergonomics Association is a book that explains related learning patterns at home for students and parents who are doing learning. In this time the Community Service is offering to provide solutions that are felt to be very much needed by students and parents in Cikeusal sub-district in terms of learning to students. Education is very important because with education there will be born a generation of knowledgeable and skilled. One effort to improve teaching done by parents and families is the variation or innovation in learning. So through community service it is necessary to share knowledge with the community, to be able to vary or innovate in every learning activity. One problem that arises in learning at home is the lack of innovative learning in implementing ergonomic cooperative learning at home. So with the problems faced by students and parents during learning at home draw conclusions for community service by providing socialization using learning media by using the ergonomics manual "Learning From Home" from the Indonesian Ergonomics Association to increase student motivation. The ergonomics manual "Learning From Home" from the Indonesian Ergonomics Association is a learning resource for Students included in the ergonomics manual "Learning From Home" from the Indonesian Ergonomics Association. In the ergonomics manual "Learning From Home" from the Indonesian Ergonomics Association contains practical materials, looks interesting, easy to carry anywhere, and able to make students focused on learning. The ergonomics manual "Learning From Home" from the Indonesian Ergonomics Association is packaged with various interesting writings and drawings so that it fosters students' motivation to learn the material in the ergonomics guidebook "Learning From Home" from the Indonesian Ergonomics Association. So for the purpose of developing this learning media by using the ergonomics manual "Learning From Home" from the Indonesian Ergonomics Association is an effort to increase students' learning motivation because of its small size and in order to increase student learning motivation.